Image-guided high-dose rate brachytherapy: preliminary outcomes and toxicity of a joint interventional radiology and radiation oncology technique for achieving local control in challenging cases - Kishan, Amar U.; Lee, Edward W.; McWilliams, Justin; Lu, David; Genshaft, Scott; Motamedi, Kambiz; Demanes, D. Jeffrey; Park, Sang June; Hagio, Mary Ann; Wang, Pin-Chieh; Kamrava, Mitchell (Journal of Contemporary Brachytherapy, 2015)
Purpose : To determine the ability of image-guided high-dose rate brachytherapy (IG-HDR) to provide local control (LC) of lesions in non-traditional locations for patients with heavily pre-treated malignancies. Material and methods : This retrospective series included 18 patients treated between 2012 and 2014 with IG-HDR, either in combination with external beam radiotherapy (EBRT; n = 9) or as monotherapy (n = 9). Lesions were located in the pelvis (n = 5), extremity (n = 2), abdomen/retroperitoneum (n = 9), and head/neck (n = 2). All cases were performed in conjunction between interventional radiology and radiation oncology. Toxicity was graded based on CTCAE v4.0 and local failure was determined by RECIST criteria. Kaplan-Meier analysis was performed for LC and overall survival. Results : The median follow-up was 11.9 months. Two patients had localized disease at presentation; the remainder had recurrent and/or metastatic disease. Seven patients had prior EBRT, with a median equivalent dose in two Gy fractions (EQD2) of 47.0 Gy. The median total EQD2s were 34 Gy and 60.9 Gy for patients treated with monotherapy or combination therapy, respectively. Image-guided high-dose rate brachytherapy was delivered in one to six fractions. Six patients had local failures at a median interval of 5.27 months with a one-year LC rate of 59.3% and a one-year overall survival of 40.7%. Six patients died from their disease at a median interval of 6.85 months from the end of treatment. There were no grade ≥ 3 acute toxicities but two patients had serious long term toxicities. Conclusions : We demonstrate a good one year LC rate of nearly 60%, and a favorable toxicity profile when utilizing IG-HDR to deliver high doses of radiation with high precision into targets not readily accessible by other forms of local therapy. These preliminary results suggest that further studies utilizing this approach may be considered for patients with difficult to access lesions that require LC.